Functional uni‐ventricular heart due to post‐myocardial infarction ventricular septum rupture. Issue 3 (21st February 2022) - Gaisendrees, Christopher; Hoffmann, Fabian; Kuffer, Liz; Mader, Navid; Wahlers, Thorsten
Abstract: Ventricular septum defect (VSD) is an often lethal complication caused by myocardial infarction. We report a rare case of post‐myocardial infarction ventricular septum rupture in a patient after extracorporeal cardiopulmonary resuscitation (eCPR). In the bedside echocardiography after VA ECMO cannulation, we noticed the circular, hypertrophied left ventricle with the disintegrated inter‐ventricular septum (maximum dehiscence 3.3 cm), accompanied by decreased left‐ventricular ejection fraction and the right ventricle being compressed by the left ventricle's free septal wall. There was no pressure‐relevant inter‐ventricular separation resulting in left‐to‐right‐shunting and therefore resulting in a fully functional uni‐ventricular heart.